Privacy preserving for electronic health record systems - Yussuf, Zakariye Mohamed (2019)
Electronic Health Records (EHR) made it easier to manipulate and manage health records in health centers, it enables many medical institutions to exchange the EHR with ease. However, as the architecture of these services become complicated, it introduces new security threats, for instance privacy of patient’s data and information when EHR is exchanged between institutions and users. In order to keep the patient’s information private, many systems and methods have been proposed to implement access control to the health records of patients. However, most of the recent approaches don’t state the importance of strong authentication, don’t support fine-grained access control and also do not take into account the encryption of data in the server. Consequently, this research proposes an EHR system that works with attribute-based access control using PHP Laravel framework. The proposed system provides multi-factor authentication, access control and also encrypts EHRs.